Job Satisfaction as a Mediator of Compensation and Leadership Style on Digital Workforce Performance in Indonesian Tech Startups - Muhamad Al Faruq Abdullah; Wenny Desty Febrian (Dinasti International Journal of Education Management and Social Science, 2025)
This study investigates the effect of compensation and leadership style on employee performance, with job satisfaction as a mediating variable, among digital workers in Indonesian tech startups. Using a quantitative approach, data were collected from 200 respondents through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that compensation has both direct and indirect effects on performance, while leadership style affects performance only indirectly through job satisfaction. Job satisfaction plays a significant mediating role, reflecting how psychological well-being connects compensation and leadership with performance outcomes. The model demonstrates strong explanatory power (R² = 0.643) and predictive relevance (Q² = 0.457), confirming the robustness of the proposed framework. These findings highlight the importance of integrating structural, relational, and psychological factors to improve performance in dynamic digital work environments.